Prarancangan Pabrik Polistirena Dengan Proses Polimerisasi Larutan Kapasitas 70.000 Ton/Tahun - Nayomi, Dela, Ir. Haryanto.A.R, M.S, M. Mujiburohman, S.T., M.T., Ph.D (2016)
Polystyrene is a thermoplastic polymer using raw materials of styrene monomer with assisted solvent ethyl benzene and benzoyl peroxide initiator. Particularly High Impact polystyrene has a number of uses as household appliances, food wrapping, insulation, and furniture. Needs of polystyrene in Indonesia is quite high from 2006-2015 are likely to experience increased. Polystyrene plant capacity of 70.000 tonnes/year operation for 330 days. In the manufacture of polystyrene comparison between raw materials, solvents of 1:0,05492. The reaction that occurs in the manufacture of polystyrene that is an exothermic reaction using reactor CSTR (Continous Stirred Tank Reactor) because the converted liquid-liquid. Operating conditions are maintained at a temperature of 90°C (isothermal) and a pressure of 1 atm. Polystyrene plant with a capacity of 70.000 tonnes/year using the raw materials of styrene monomer of 12.575,8271 kg/h ethyl benzene of the impurities with 50,5053 kg/h ethyl benzene solvent, to of 690,6644 kg/h with the impurities of toluene and benzene respectively amounted to 0,0691 kg and 0,6222 kg/h, and benzoyl peroxide initiator of 20,5071 kg/h. In the manufacture of polystyrene requires supporting units namely air, steam, electric, and compressed air. For the needs of water obtained from the River as much as 3.249,4677 kg/h. Steam needs as much as 659,3500 kg/h of boiler with diesel fuel as much as 0,0607 m3/hour. Electricity needs as much as 335,6026 kW obtained from PLN and as a backup generator that has a capacity of 1.000 kW using fuel as much as 0,1145 m3/hour. Compressed air needs as much 71.064 m3/hour. This direnacanakan the factory located in Serang, Banten, with a land area of 14,800 m2 and employs 128 people. Economic analysis of polystyrene plant is in need of fixed capital amounted to Rp 297.722.649.279 and Rp 148.745.508.634 of working capital. While profit before tax of Rp. 131.171.167.310/year. Profit after tax of Rp 101.378.375.483/year. This feasibility analysis it can be concluded that the Percent Return On Investment (ROI) of 45,40% before tax and after tax of 34,05%. Pay Out Time (POT) before tax of 1,80 years and after tax of 2,27 years. Break Even Point (BEP) of 41,48% capacity and Shut Down Point (SDP) of 27,30% capacity. Discounted Cash Flow (DCF) for 31,75%. Based on the analysis of the feasibility of the polystyrene plant is quite interesting and worth to be established.